SPATIO-TEMPORAL VARIABILITY OF PRECIPITATION IN THE VENEZUELAN AMAZON - Manuel Villa, Pedro (2022)
The Amazon region has a fundamental role in the global hydrological balance. Thus, the spatial and temporal precipitation analyses are essential to evaluate the impacts of climate change. However, there is still an information gap in the Venezuelan Amazon. This research aimed to analyze the spatial and temporal patterns of twelve years (2000-2011) of precipitation data from ten sites in the Venezuelan Amazon. The spatial and temporal structures of interannual precipitation variability were analyzed. The Mann-Kendall non-parametric test was used to determine if annual precipitation trends at each site can be identified using a time series that includes a seasonal component. The global Moran index was used to evaluate spatial autocorrelation of precipitation between observations based on Era-Interim. When the 10 sites were separated into groups of average annual precipitation, two homogeneous groups of precipitation were distinguished. The monthly precipitation at each site also defined the homogeneous precipitation groups. These results showed that in this region of the Amazon a unimodal pattern of precipitation predominates at the different sites, with a long period of precipitation and a period with less precipitation between December and March. This pattern is explained by the Intertropical Convergence Zone, which is shifted to more southern latitudes during these months, thus modifying the precipitation dynamics in the Amazon. Furthermore, the main consequences in the precipitation pattern in the Amazon are the influence of the South Atlantic Convergence Zone with the occurrence of high precipitation. Assessing the local spatial association by ERA-Interim, it is noted that the clusters of precipitation (Moran index) express the variability as a function of the significance level of the local indexes’ values.